Development of Audio Visual Based PAI Teaching Materials to Increase Learning Motivation for Class V Students at SDN Panaguan 3 Kec. Proppo - Tika Hestiarini Utami; Nurul Zainab (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2024)
In order to enhance students’ learning motivation, it is necessary to use instructional materials that have the ability to captivate students’ attention. The objective of this study is to provide audio-visual Islamic Religious Education instructional resources with the aim of enhancing the learning motivation of 5th grade students at Panaguan 3 State Elementary School in the Proppo District. This study utilises a Research and Development (R&D) approach. Data was gathered through the utilisation of observation, interview, and questionnaire methodologies. The data obtained from the surveys, which consist of numerical values and percentages, will be subjected to descriptive analysis. The research findings demonstratethat the canva programme was used to create audio-visual-based teaching materials for Islamic Religious Education, specifically focusing on chapter 6 titled “Leaving Peacefully in Togetherness”. The learning materials passes the requirements of being highly practicable to use as the results of the media expert validation questionnaire are 90% (very feasible), linguist validation 90%(very feasible), and material expert validation 95% (very feasible). While the results of the student assessment questionnaire through the three sections of the assessment attained an average value of 95% ehich suggests that this learning material is very attractive to students’ attention and interest in learning so that it could increase student learning motivation.